2008
DOI: 10.1007/s12185-008-0196-y
|View full text |Cite
|
Sign up to set email alerts
|

Use of micafungin versus fluconazole for antifungal prophylaxis in neutropenic patients receiving hematopoietic stem cell transplantation

Abstract: A prospective randomized clinical trial assessed the efficacy and tolerance of micafungin compared with that of standard fluconazole treatment in patients undergoing hematopoietic stem cell transplantation (HSCT). Adult patients (n = 106) were randomly assigned to receive prophylaxis with either micafungin 150 mg (n = 52), or fluconazole 400 mg (n = 52). Success was defined as the absence of suspected, proven, or probable invasive fungal infection (IFI) through the end of therapy and the absence of proven or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 22 publications
7
60
0
1
Order By: Relevance
“…This was consistent with breakthrough rates ranging between 5.3% and 7.3% reported in antifungal prophylactic clinical trials [1,2,[15][16][17]. One breakthrough bloodstream infection with Rhodotorula species was identified, which was consistent with the susceptibility profile of this organism [18].…”
Section: Discussionsupporting
confidence: 86%
“…This was consistent with breakthrough rates ranging between 5.3% and 7.3% reported in antifungal prophylactic clinical trials [1,2,[15][16][17]. One breakthrough bloodstream infection with Rhodotorula species was identified, which was consistent with the susceptibility profile of this organism [18].…”
Section: Discussionsupporting
confidence: 86%
“…7,20 The treatment efficacy of micafungin in this study was comparable to that of micafungin prophylaxis reported in adult populations. 7,17 Furthermore, micafungin showed 100% efficacy for preventing any proven fungal infection, not only during the neutropenic phase but also 4 weeks after stopping micafungin prophylaxis.…”
Section: Discussionsupporting
confidence: 78%
“…Echinocandins were used as primary prophylaxis in eight studies and as secondary prophylaxis in one study (Table 1) [25][26][27][28][29][30][31][32][33]. Underlying diseases of the study populations are presented in Table 1.…”
Section: Breakthrough Mycoses With Echinocandin Use As Antifungal Promentioning
confidence: 99%